J is for Jawfest - 10 Erotic Short Stories - Stigsdotter, Saga (Saga Egmont, 2023)
Part of the erotic alphabet series, 'J is for Jawfest - 10 Erotic Short Stories' is a collection of erotica that might just give you a sore jaw with all the fellatio and blowjobs on offer.